Theoretical Study of Diffusion and Adsorption Inside Nano- and Mesoporous Active Particles - Klymenko, O. V. (ХНУРЭ, 2008)
Mass transport of a target species towards and within spherical mesoporous organosilica particles and its adsorption by active sites at pore walls is investigated through the numerical solution of the pertinent mathematical model. The presented theoretical results allow the optimization of mesoporous materials to increase their capacity towards target ions or molecules and their time-efficiency.
Keywords: nanopore; adsorption; desorption; numerical simulation